Analysis of Student Interest in Using Video Media in Learning - Darwin; Haratua Tiur Maria S; Venny Karolina (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2023)
This research is entitled Analysis of Students' Interest in Using Video Media in Learning at SMAN 1 Toho, with the aim of assessing the extent of students' interest in using video media in learning. Specifically, this research aims to evaluate significant differences in the use of learning video media between male and female students, as well as assess significant differences between class X in the use of learning video media. This type of research is quantitative with quantitative descriptive methods, carried out at SMA Negeri 1 Toho in September 2023 involving 106 class X students, consisting of Class Xa (28 people), Class Xb (25 people), Class Xc (27 people), and Class Xd (26 people), with the entire population used as the research sample. Data collection was carried out through a questionnaire in the form of a questionnaire with 18 positive statements using a Likert scale and filled in via Google Form. The results of the analysis show that the learning interest of class X students at SMA Negeri 1 Toho is moderate in using video media in the learning process. Factors that influence interest involve external and internal attractiveness, while the use of learning media that is less attractive also has a negative impact on student interest. Teachers' lack of understanding and skills in utilizing learning media also plays a role in reducing student interest. Even though there is no significant difference between the interests of male and female students, there are striking differences between classes in using video learning media. Therefore, it is recommended that teachers increase creativity in designing learning by utilizing videos to increase students' interest and enthusiasm in the learning process.